Se-Regulated MnS Porous Nanocubes Encapsulated in Carbon Nanofibers as High-Performance Anode for Sodium-Ion Batteries - Puwu Liang; Duo Pan; Xiang Hu; Ke R. Yang; Yangjie Liu; Zijing Huo; Zheng Bo; Lihong Xu; Junhua Xu; Zhenhai Wen (Nano-Micro Letters)
Highlights We have developed an efficient and scalable strategy to prepare a single-phase ternary MnS0.5Se0.5-carbon nanofiber composite with a defect-rich microstructure. The Na+ storage mechanism of manganese-based sulfides after the incorporation of Se was thoroughly investigated, through systematic electrochemical characterization combined with theoretical calculations. The MnS0.5Se0.5@N-carbon nanofiber composite, used as an anode, exhibits excellent reversible capacity, rate capability, and cycling stability in sodium-ion batteries.